Alat Monitoring Detak Jantung Untuk Pasien Beresiko Berbasis IoT Memanfaatkan Aplikasi OpenSID berbasis Web - Y Yuhefizar; Anggara Nasution; Roni Putra; Ervan Asri; Deni Satria (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Patients with arrhythmia symptoms must undergo a healthy lifestyle and routinely conduct consultations and heart rate control with the doctor. The most important thing about this is the integrated health monitoring tool. In this study a portable heart rate monitoring tool is proposed for patients at risk of low-cost IoT-based with SMS alert system utilizing the OpenSID database. . Module ESP8266 Wi-Fi is used to communicate the web server gateway and pulse sensor to detect the heart rate which converted to Bit per Minute (BPM). Heart rate data is saved to the database server using TCP IP communications. Patients and doctors can see heart rate information trough the website in real-time. Alert system will send notification information via short message service (SMS ) to doctors, person in charge and family if heart rate below 60 BPM and above 100 BPM. the time needed for sending SMS is about 7 to 8 seconds. Test results show the whole system is running well. This tool is expected can accompany the risk patients do their activities safely and both doctors and families easier to supervise the patients.